Sustainable solid polymer electrolytes based on NaCMC-PVA blends for energy storage applications: electrical and electrochemical insights with application to electric double-layer capacitors - Cyriac, Vipin; Ismayil; Mishra, Kuldeep; Rao, Ankitha; Masti, Saraswati P.; Noor, I. M. (John Wiley and Sons, 2025)
This research proposes a novel biopolymers’ blend-based solid polymer electrolyte (SPE) for electric double-layer capacitors (EDLCs). Flexible SPE films are fabricated by immobilizing sodium hexafluorophosphate (NaPF6) salt in a blend of sodium carboxymethyl cellulose and poly (vinyl alcohol) using a solution-casting technique. The study employed X-ray diffraction, Fourier-transform infrared spectroscopy, scanning electron microscopy, and atomic force microscopy techniques to evaluate the structural and morphological characteristics. The electrolyte system exhibits a maximum ionic conductivity of 2.26 × 10−5 S cm−1 with a substantial electrochemical stability window of ≈3.56 V. Frequency-dependent electrical studies elucidate the ion dynamics of the electrolyte systems in accordance with the structural modifications within the system. The optimized electrolyte sample is employed in an EDLC device, and various performance parameters are obtained. The device demonstrates a specific capacitance of 9.53 F g−1, energy density of 0.979 W kg−1, and a power density of 43 Wh kg−1 at a current density of 0.1 mA g−1 and exhibited reliable performance for 3000 cycles.